Removal of arsenic from ground water by modified Sabzevar zeolite - Fatemeh Hoveidamanesh; Zahra Beagom Mokhtari-Hosseini; Toktam Shenavaei Zare; Hashem Akhlaghi (Journal of Applied Research in Water and Wastewater, 2025)
The existence of arsenic in water is one of the main problems of the world, especially in developing countries. One of the methods suggested for removal of arsenic is the use of adsorbents. In this study, natural Sabzevar zeolite was modified with HDTMA-Br, HCl, NaCl and FeCl3.6H2O for the adsorption of arsenic. It was found that zeolite modified with FeCl3.6H2O was best for the removal of arsenic. Contact time (h), pH, zeolite particle size (mesh) and amount of zeolite (g) as the important parameters were optimized by Taguchi method. The optimum values for these parameters were contact time of five h, pH=3, and 100-200 mesh particles. The maximum adsorption capacity of 99.5% was obtained at optimum condition. Reactivation of the modified zeolite using HCl showed that the reactivated zeolite adsorbed 98% of the arsenic, a slight decrease compared to the original material. The presented adsorption process is a green and economical process for removing arsenic from water and contaminated groundwater.